Light‐Emitting Field‐Effect Transistors Having Combined Organic Semiconductor and Metal Oxide Layers. (9th April 2013) - Yamada, Keisei; Yamao, Takeshi; Hotta, Shu
<x xml:space="preserve">Abstract</x> A new organic light‐emitting field‐effect transistor characterized by a metal oxide layer inserted between the organic layer and the gate insulator is proposed. The metal oxide is indirectly connected with source and drain electrodes through the organic layer. Upon increasing the potential difference between the source and drain electrodes, the emission becomes exceedingly strong and the emission region encompasses the whole channel zone. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>